1989
DOI: 10.1002/j.1556-6676.1989.tb02488.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Counselor Preference Among Gays and Lesbians

Abstract: This study explored the preference for counselor's sexual orientation among gay and lesbian clients. Recognizing that the perceived reaction of participants to hypothetical situations may be a viable predictor of future choices, respondents were administered a comfort/discomfort index intended to probe a number of potential counseling concerns. Internalized homophobia (Hudson & Ricketts, 1977) and a scale measuring degree of same‐ or opposite‐sex sexual preferences (Kinsey, Pomeroy, Martin, & Gebbhard, 1953) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 7 publications
(7 reference statements)
0
23
2
Order By: Relevance
“…Whereas some research on the importance of counselor sexual orientation in counseling emphasizes LGB clients' preferences for LGB counselors (McDermott, Tyndall, & Lichtenberg, 1989;Modrcin & Wyers, 1990), others report that matching counselor sexual orientation with that of one's client does not increase LGB clients' ratings of the counselor (Liddle, 1996). The present study revealed that counselors disclosing homosexual as opposed to heterosexual orientation were perceived as significantly more attractive.…”
Section: Discussioncontrasting
confidence: 47%
“…Whereas some research on the importance of counselor sexual orientation in counseling emphasizes LGB clients' preferences for LGB counselors (McDermott, Tyndall, & Lichtenberg, 1989;Modrcin & Wyers, 1990), others report that matching counselor sexual orientation with that of one's client does not increase LGB clients' ratings of the counselor (Liddle, 1996). The present study revealed that counselors disclosing homosexual as opposed to heterosexual orientation were perceived as significantly more attractive.…”
Section: Discussioncontrasting
confidence: 47%
“…The impact of biases against LGBT individuals that may exist in their substance abuse treatment providers has not been studied. A survey found that 59% of LGBT respondents expressed a preference for LGBT counselors (McDermott, Tyndall, & Lichtenberg, 1989). This may indicate that LGBT individuals fear that heterosexual counselors would misunderstand or, worse, actively discriminate against them based on their sexual identities.…”
Section: Substance Abuse Treatment For Lgbt Individualsmentioning
confidence: 98%
“…This representation, in such a small sample, supports not only the need for this type of supervisory experience (see Clark, 1977;McDermott et al, 1989), but also the reality that bisexual and transgender experience are essential, though neglected, elements of the supervisory literature.…”
Section: Characteristics Of the Groupmentioning
confidence: 60%
“…In fact, Clark (1977) and McDermott, Tyndall, and Lichtenberg (1989) recommend that sexual minority-oriented supervision be employed for sexual minority clinicians.…”
mentioning
confidence: 97%